Islamic Education in Thailand: Implementation of Islamic Values at Torphanrojjanawich School, Satun, Thailand - Fabianto, Eko; Aeni, Gadis Inayatul; Tapee, Nuruema (International Journal of Local and Global Islamic Dynamics, 2025)
Although Islam is a minority religion in Thailand, it holds a dominant presence in the southern region, where numerous Islamic schools integrate religious values into their teaching and learning processes. These institutions educate students in Islamic principles from early childhood, starting at the kindergarten level and continuing through high school. The aim is not only to provide academic instruction but also to instil core Islamic values in students. This study sought to explore how Islamic values are taught within the Thai educational context. A descriptive qualitative method was employed, with data collected through observations, interviews, and document analysis. The research was conducted at Torphanrojjanawich School in Satun, Thailand, between November 2024 and January 2025. Data analysis followed steps including data condensation, presentation, verification, and conclusion drawing. The findings revealed that students at the school engaged in various learning activities. Academically, instruction was based on a school-specific curriculum rather than the Thai national curriculum. Religiously, the educational focus centred on Islamic principles such as faith, worship, and moral behaviour. This research aims to serve as a reference for implementing Islamic education in contexts where Muslims are a minority.